2018
DOI: 10.1055/s-0037-1618571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the von Willebrand Factor Gene in Swedish von Willebrand Disease Patients

Abstract: Abstractvon Willebrand factor (VWF) level and function are influenced by genetic variation in VWF and several other genes in von Willebrand disease type 1 (VWD1) patients. This study comprehensively screened for VWF variants and investigated the presence of ABO genotypes and common and rare VWF variants in Swedish VWD1 patients. The VWF gene was resequenced using Ion Torrent and Sanger sequencing in 126 index cases historically diagnosed with VWD. Exon 7 of the ABO gene was resequenced using Sanger sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Thus, the historic type 1 VWD population is very similar to our type 1 VWD population where 48% of the patients had rare VWF variants and 70% had blood group O. 17 There are clear differences between VWD populations defined using historic and contemporary definitions. For example, Sanders et al 7 compared the A-allele frequency of rs9390459 in their type 1 VWD population (0.47) with that of healthy individuals in the CHARGE study (0.44).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, the historic type 1 VWD population is very similar to our type 1 VWD population where 48% of the patients had rare VWF variants and 70% had blood group O. 17 There are clear differences between VWD populations defined using historic and contemporary definitions. For example, Sanders et al 7 compared the A-allele frequency of rs9390459 in their type 1 VWD population (0.47) with that of healthy individuals in the CHARGE study (0.44).…”
Section: Discussionsupporting
confidence: 61%
“…The 127 unrelated patients have been characterized with respect to their VWF mutations. 17 Previous deoxyribonucleic acid (DNA) sequencing have identified mutations in 20 type 2 VWD patients among the 127 patients initially diagnosed with type 1 VWD. The remaining 107 type 1 VWD patients (76 females and 31 males) have been analysed in this study.…”
Section: Study Populations and Vwd Phenotypingmentioning
confidence: 99%
“…The sequencing detected a total of 146 variants in the coding sequences of the eight genes. Excluding 70 variants in VWF (described in detail in the study by Manderstedt et al), 8 76 variants remained. There were a total of 19 variants in ABO : eight missense, two frameshift, and nine synonymous.…”
Section: Resultsmentioning
confidence: 99%
“…VWF harbored 70 of these, of which many were mutations and have been described in detail previously. 8 Of the remaining 76 variants, 54 had allele frequencies > 0.5% and a majority of these have therefore likely already been investigated for their association with the VWF level in later GWAS also investigating low-frequency variants in these and other genes. 4 6 The rs141041254 STAB2 variant associated with VWF level variation and identified by Huffman et al 4 was not found in this study, but it has been further investigated along with common variants in STAB2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation